Scenario-Based e-Simulation Design for Global Health Education: Theoretical Foundation and Practical Recommendations - Awsan Bahattab; Marta Caviglia; Daniela Martini; Ives Hubloue; Francesco Della Corte; Luca Ragazzoni (JMIR Publications, 2023)
Electronic simulation (e-simulation)-particularly scenario-based e-simulation (SBES)-is an increasingly used, promising educational strategy for global health education that can address gaps in training access, effectiveness, and cost. However, there is little guidance for educators on how to develop an SBES, and guidance is lacking outside the clinical context. Moreover, literature on medical education rarely uses the theoretical basis for e-simulation design and development, including for SBES. Hence, we aim to differentiate and describe the concept, design elements, and theoretical basis of SBES with examples from different topics in global health. In addition to enhancing the understanding of the potential of SBES for global health education, this manuscript also provides practical recommendations for global health educators in designing and developing SBESs based on the existing literature and authors' experiences. Overall, this manuscript will be useful for global health educators as well as other medical educators seeking to develop an SBES for similar skill sets.